Does MRI help in retaining potency in fracture penis? (International Journal of Biomedical Research, 2014)
Introduction: Penile fracture is a rare but urological emergency which requires expediate surgical treatment for restorement of potency. This condition remains under-reported due to ethical and psychological reasons. Diagnosis of penile fracture is mainly based on clinical features. MRIof thepenisis an expensive test that is not always superior to clinical examination or ultrasound. However, it shows many of the important structures and in particular the high-resolution T(2) sequences show the glans, corpora and the tunica albuginea well. Our aim was to review whether MRI helped in early diagnosis and thereby helping in restoring potency. Material and methods: From May 2009 to October 2013, 6 patients with fracture penis were treated at our institute. Mean age of patients was 32.83 years, range from 24 to 43. All the patients presented after 6 hours of injury. Results: Patients who presented early had good IIEF score at three months compared to those who presented late. MRI helped in diagnosing the fracture in two cases, which would have otherwise been treated conservatively. Conclusions: Rupture of the corpus cavernosum is a rare condition and is generally diagnosed by clinical findings. Emergency surgical exploration and treatment is the best guarantee of good functional and cosmetic result.